Wood related chemical markers of aged wine brandies - Canas,S. (2008)
Several low molecular weight phenolic compounds - phenolic acids, phenolic aldehydes, coumarins, acetovanillone and ethyl vanillin - were quantified by HPLC in Portuguese wine brandies aged four years in Portuguese oak (Quercus pyrenaica Willd.), Allier oak (Quercus sessiliflora Salisb.) and chestnut (Castanea sativa Mill.) wooden barrels (250 L), in order to identify those of chemical markers of the wood botanical species. The results obtained demonstrated that gallic acid, ellagic acid, ferulic acid, scopoletin, acetovanillone and ethyl vanillin play that role in the aged brandies. Gallic acid and acetovanillone present the highest contents in the brandies aged in chestnut, while ethyl vanillin exhibit the highest content in the brandies aged in oak woods. The differentiation of the brandies aged in oak woods is made by ellagic and ferulic acids, whose contents are higher in Portuguese oak, and by scopoletin that predominates in the brandies aged in Allier oak. Complementary, a practical and reproducible HPLC method was validated allowing a good separation and quantification of acetovanillone and ethyl vanillin in wine aged brandies.